Reverse engineering of graphical user interfaces - Inês Coimbra Morgado (2011)
This paper describes a dynamic reverse engineering approach and a tool (ReGUI) that were developed with the aim of reducing the effort to obtain a visual and formal model of the structure and behaviour of a software applications GUI. Once produced, the model must be completed, checked and validated to ensure that it faithfully describes the intended system. These models are used as a test oracle and as input to a test case generation tool in the context of the AMBER iTest project, in which model based testing techniques are applied with GUI testing purposes.